SOCIO-PSYCHOLOGICAL CONDITIONS OF PREVENTION OF EMOTIONAL BURNOUT BY SOCIAL WORKERS - O. Kolosova; K. Remizova (Вестник университета)
The article describes research of the emotional burnout by social workers. Burnout defines as a syndrome of emotional and physical fatigue, tired and exhausted. It is a serious problem for the person and his mental health, so the authors reveal various ways how to fight this syndrome. One of the ways to effectively prevent burnout can be different types of training exercises, seminars that will help social workers to acquire skills of self-regulation. The study shows that the creation of socio-psychological conditions has a positive impact on the emotional and social health of the specialist.